(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The historic region of Hadoti in the state of Rajasthan in India showcases a rich and prosperous history from prehistoric times to the modern era. The Kota princely state was one of the prominent princely states of Rajasthan. The Kota princely state included the territories of Bundi, Jhalawar, and Kota districts. On March 31, 1949, Rajasthan was reorganized. The headquarters of the Baran district was made a sub-divisional headquarters of the Kota district. On April 10, 1991, Baran district was created from the former Kota district.